2015
DOI: 10.1016/j.joca.2015.02.100
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel, locally delivered TrkA inhibitor in preclinical models of OA and joint pain

Abstract: KO mice showed reduced expression of MMPs. This correlates well with our finding that stimulation of human OA synovium with WISP1 led to increased MMP expression. TGF-b signaling via Smad 2/3 is crucial for maintaining the homeostasis of the cartilage, while signaling via Smad 1/5/8 is associated with chondrocyte hypertrophy. In order to determine if WISP1 affects TGF-b signaling, we stained WT and WISP1 depleted joints for phosphorylated Smad 2/3. We found that Smad 2/3 signaling was increased in the WISP1 KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Another TrkA inhibitor (GZ389988) has been developed by Sanofi, formulated for IA administration to control OA pain. In the rat MIA model, a single IA injection of GZ389988 resulted in more normal weight‐bearing for four weeks without any significant histopathological changes in joint tissues compared with placebo 103 . Interestingly, IA injection into the contralateral joint had no effect on the ipsilateral limb joint pain, suggesting that IA injection does not result in substantial systemic exposure, which may limit the risk of AEs.…”
Section: Monoclonal Antibodies Targeting Ngfmentioning
confidence: 99%
“…Another TrkA inhibitor (GZ389988) has been developed by Sanofi, formulated for IA administration to control OA pain. In the rat MIA model, a single IA injection of GZ389988 resulted in more normal weight‐bearing for four weeks without any significant histopathological changes in joint tissues compared with placebo 103 . Interestingly, IA injection into the contralateral joint had no effect on the ipsilateral limb joint pain, suggesting that IA injection does not result in substantial systemic exposure, which may limit the risk of AEs.…”
Section: Monoclonal Antibodies Targeting Ngfmentioning
confidence: 99%
“…GZ389988A is insoluble in water and has been formulated as an aqueous suspension for intra-articular (IA) injection, aiming at sustaining pain reduction and reducing systemic exposure. In rat models of OA and joint pain, GZ389988 showed a significant relief of local knee pain 28 .…”
Section: Introductionmentioning
confidence: 94%
“…GZ389988 was tested in animal OA models, and a 4-week efficacy was observed (the entire observation period due to limitations of animal models 28 ). With this, it was predicted hypothetically that the duration of efficacy in humans could be around 2.5 months.…”
Section: Assessmentsmentioning
confidence: 99%
“… Reversion of the weight-bearing asymmetry of rats with MIA after 7 days from TrkAd5 inhibitor treatment. Adverse effects were not evaluated Flannery 2015 20 Pain assessment Rat model of MIA Anti-NGF mAb 9 mg/kg, 2 days after MIA induction (s.c.) Reversion of the rat MIA model burrowing deficit after 3 days from mAb treatment. Adverse effects were not evaluated Bryden 2015 21 Pain and joint assessment Rat model of OA Anti-NGF mAb AS2886401-00 0.3 or 1 mg/kg on day 3 (i.v.)…”
Section: In Vivo Preclinical Studies On the Effects Of Anti-ngf Mabs In Animal Models Of Chronic Pain: An Updatementioning
confidence: 99%
“…Similar findings were presented by Flannery et al in a rat mono-iodoacetate (MIA) model. 20 Bryden et al demonstrated that a subcutaneous injection of anti-NGF mAb, in a rat MIA model, reversed deficits in burrowing compared to non-treated mice. 21 To date, few preclinical studies conducted on animal models of chronic pain have assessed both pain and joint changes after anti-NGF mAb treatment.…”
Section: In Vivo Preclinical Studies On the Effects Of Anti-ngf Mabs In Animal Models Of Chronic Pain: An Updatementioning
confidence: 99%